Examining human-AI interaction in real-world healthcare beyond the laboratory - Wekenborg, Magdalena Katharina; Gilbert, Stephen; Kather, Jakob Nikolas (npj digital medicine, 2025)
Artificial Intelligence (AI) is revolutionizing healthcare, but its true impact depends on seamless human interaction. While most research focuses on technical metrics, we lack frameworks to measure the compatibility or synergy of real-world human-AI interactions in healthcare settings. We propose a multimodal toolkit combining ecological momentary assessment, quantitative observations, and baseline measurements to optimize AI implementation.
Gesehen am 21.10.2025